Revisiting Purchasing Power Parity of Papua New Guinea - Liew, Venus Khim-Sen; Ling, Tai-Hu; Chia, Ricky Chee-Jiun (IPEDR, 2011)
Studies on long-run Purchasing Power Parity (PPP) for Papua New Guinea (PNG), one of the least developed countries in the world, is limited. Unlike the two existing studies, which consistently show no support for PPP, this note uncovers evidence of PPP for Papua New Guinea (PNG). Results from further analysis indicates that nominal exchange rates and relative prices are nonlinearly interrelated. This PPP in nonlinear dynamic fails to be detected in previous studies that did not include nonlinear analysis. Frictions in international trade could be behind the establishment of the above-mentioned nonlinear relationship.